Design of a scale physical model of a road train for experimental research (ADVANCES IN MECHANICAL ENGINEERING AND TRANSPORT, 2021)
Carrying out research on controllability and maneuverability on real road trains has many difficulties and requires significant material and time resources. They are also associated with potentially dangerous test situations. The article is devoted to the design of a large-scale physical model of a long-base road train that would have universal modules. The modular principle allows it to quickly change over to different configuration schemes. The design of a large-scale physical model and used electronic modules is described in detail. The model has an independent electric drive on the drive wheels, controlled by a microcontroller. Model equipped with measuring, recording and remote control equipment for experimental study of the properties of controlled road trains.Based on the main provisions of the theory of similarity, it follows that if two dynamical systems are described by the same differential equations, then the solution of differential equations will be large invariant for the same groups. For the model to be dynamically similar to the original, the values of these groups must be the same for both systems. Based on this idea, it can determine the parameters of the model that correspond to the real object.In the future it is planned to conduct a comparative analysis of the results of theoretical research on a mathematical model and the results of experimental research on a large-scale physical model. And also checking the adequacy of the mathematical model.Key words: road train, scale, physical model, controllability, maneuverability, experiment, controller, dual drive.